Examining polarizing and non-polarizing filters for road sports - Mercatelli, Luca (Frontiers in Sports and Active Living, 2023)
The use of sunglasses and polarized sunglasses is common in all aspects of life and is very popular in outdoor athletic activities , . However, the athletes' choice regarding their sunglasses is often not dictated by the performance ensured by one model rather than another, but by other factors such as look or wearability, due also to the lack of technical data on catalogues. A conscious choice of filters to use, also according to road and weather conditions, supported by quantitative data, would instead give athletes the opportunity to improve their visual comfort and sports experience. The transmission spectrum of ten pairs of sport sunglasses (five polarized and five not) was measured and related to the road luminance for different sun positions both in horizontal and vertical polarizations. The luminous transmission factor was calculated and the luminance quantities while wearing the glasses were defined and calculated for all cases. A survey was submitted to a group of athletes to collect their impressions and relate them to the measurements results. The pairs of polarized and non-polarized sport sunglasses showed similar transmission factors so that their ability to mitigate outdoor light is almost the same, the main difference consisting in the polarized light transmitted. Outdoor measurement showed that the light reflected by the road has a substantial polarized horizontal component. Large part of the light reflected by the road is then blocked by polarized sunglasses, thus the road appears darker, diminishing the glare of the scene in bright sunlight. The road luminance decrease gives an increase in the contrast discrimination of other objects of the scene which reflect sunlight in a non-polarized way, (e.g., non-flat surfaces). The survey demonstrates that for those reason interviewed athletes prefer polarized sunglasses. This study highlights the advantages of polarizing sunglasses for athletic activities performed on roads because in many conditions, depending on the position of the sun, the road surface reflects polarized light.